Teams Game Tournament (TGT) Method In Mathematics Subject Multiple Material In Class IV MI Hidayatus Sibyan Tuban - Nining Puji Lestari; Nur'im Septi Lestari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
In general, mathematics is a subject that is considered difficult and disliked by students. Mathematics is difficult to understand, understand and learn, so mathematics lessons become scary, boring and less attractive to students. So that the impression is gradually lost, teachers are required to be willing and able to design and implement learning activities that attract students' interest and attention. The TGT method was first developed by David De Vries and Keith Erdward. Multiplication is considered difficult by students. The Teams Game Tournament (TGT) method on multiplication material is applied in class IV MI Hidayatus Tuban. Qualitative research methods with interview, observation, and documentation techniques. The subjects of this study were all 18 students in Class IV and two teachers, the class teacher and the principal. Results showed that using the Teams Game Tournament (TGT) method improved learning outcomes of students who managed to score with a minimum standard score of KKM70 where 3 children got a score of 75 from the previous score of 45, 2 children got a score of 75 from the previous score of 55, 2 children who scored 80 from the previous 65, 2 children who scored 80 out of 70, 3 children who scored 85 from the previous 80, 2 children who scored 90 and 95 from the previous 85, and 4 children who received 100 from the previous value of 87.